Ammonia emissions from naturally ventilated dairy cattle buildings and outdoor concrete yards in Portugal - Pereira, J. (2013)
There is a lack of information on ammonia (NH3) emissions from cattle housing systems in Mediterranean countries, with most published data deriving from NW Europe. An investigation was carried out in NW Portugal to quantify NH3 emissions for the main types of dairy cattle buildings in Portugal, i.e. naturally ventilated buildings and outdoor concrete yards, and to derive robust emission factors (EFs) for these conditions and compare with EFs used elsewhere in Europe. Measurements were made throughout a 12-month period using the passive ﬂux sampling method in the livestock buildings and the equilibrium concentration technique in outdoor yards. The mean NH3 emission factor for the whole housing system (buildings þ outdoor yards) was 43.7 g NH3eN LU 1 day 1 and for outdoor concrete yards used by dairy cattle was 26.6 g NH3eN LU 1 day 1 . Expressing NH3 emission in terms of the quantity of liquid milk produced gave similar values across the three dairy farms studied (with a mean of 2.3 kg N ton-milk 1 produced) and may have advantages when comparing different farming systems. In dairy houses with outdoor yards, NH3 emissions from the yard area contributed to 69e92% of total emissions from this housing system. Emissions were particularly important during spring and summer seasons from outdoor yards with NH3 emitted in this period accounting for about 72% of annual emissions from outdoor yards. Mean NH3 emission factors derived for this freestall housing system and outdoor concrete yards used by dairy cattle in Portugal were higher than those measured in northern Europe. In addition, values of animal N excretion estimated in this study were greater than ofﬁcial National standard values. If these emissions are typical for Portuguese dairy systems, then the current National inventory underestimates emissions from this source in NW of Portugal, because of the use of lower standard values of N excretion by dairy cattle.